Incidence, mortality, survival, risk factor and screening of colorectal cancer: A comparison among China, Europe, and northern America - Li, Na; Lu, Bin; Luo, Chenyu; Cai, Jie; Lu, Ming; Zhang, Yuhan; Chen, Hongda; Dai, Min (Cancer letters, 2021)
Colorectal cancer (CRC) is one of the most common malignancies worldwide. China, Europe and northern America account for more than half of the new CRC cases and associated deaths globally. This review summarizes the current status and temporal trends of CRC in China, Europe, and northern America. The potential primary preventive strategies and latest advances in CRC screening techniques and programs are discussed. Recently, the incidence and mortality of CRC in some European and northern American countries have decreased; conversely, CRC incidence and mortality continue to increase in China. The overall 5-year relative survival rate for CRC is similar between these regions, but there is considerable heterogeneity among European countries. Implementing population-based CRC screening programs can effectively address the growing disease burden. The effectiveness of nationwide CRC screening programs in these regions has been limited by relatively low coverage and participation rate. The deployment of state-of-the-art techniques and precise risk-adapted screening strategies incorporating effective risk prediction models and screening techniques may boost screening effectiveness. Our review provides novel foundations for the development and optimization of CRC preventive strategies. •Colorectal cancer (CRC) is one of the most common malignancies worldwide.•China, Europe and northern America account for more than half of new CRC cases.•Pattern of CRC incidence and mortality varied in China, Europe and northern America.•Expanding the coverage and improving participation rate of CRC screening are needed.•Developing novel techniques and strategies may boost the effectiveness of screening.